Yöjuna = Night train : surrealistisia reittejä Kiasman kokoelmiin = surrealist routes to Kiasma's collections - KIASMA (Museum of Contemporary Art), Helsinki (2003)
Ahonen, Eino ; Ahtila, Eija-Liisa ; Bellinin Akatemia ; Berg, Hans-Christian ; Clemente, Francesco ; Ekström, Saara ; Ernst, Max ; Etkin, Suzan ; Favier, Philippe ; Florensky, Olga & Alexander ; Friberg, Maria ; Furunes, Anne Karin ; Gamdrup, Mads ; Hannula, Simo ; Harri, Juhani ; Heiskanen, Outi ; Hernandez, José ; Hernández, Julio L. ; Hietanen, Helena ; Jaakola, Alpo ; Junno, Tapio ; Juvonen, Jari ; Kaikkonen, Kaarina ; Kanervo, Marja ; Karhu, Mika ; Kaskipuro, Pentti ; Kella, Marjaana ; Kivinen, Markku ; Kolar, Jiri ; Koskinen, Pentti Otto ; Kounellis, Jannis ; Kahre, Markus ; Larjosto, Harri ; Laukkanen, Irma ; Lumikangas, Pentti ; Mahn, Inge ; Merenmies, Elina ; Mäkilä, Otto ; Mäntynen, Taru ; Nieminen, Antti ; Nyqvist, Thomas ; Oja, Marjatta ; Oskar, Jón ; Oursler, Tony ; Paladino, Mimmo ; Pyykkö, Kimmo ; Raetz, Markus ; Ratalahti, Antti ; Rauhala, Osmo ; Rekula, Heli ; Renvall, Seppo ; Roberts, Liisa ; Ruotsala, Maria ; Savolainen, Alli ; Scharmanoff, Magnus ; Sherman, Cindy ; Sidén, Ann-Sofi ; Siikamaki, Arvo ; Smith, Michael ; Snedsbol, Erik ; Somma, Ossi ; Suomi, Risto ; Tapiola, Marjatta ; Urbonas, Gediminas ; Uutinen, Marianna ; Wall, Jeff ; Whitehead, Oliver ; Wirkkala, Maaria ; Virtanen, Petri
biog. p. 108-132
Engels
Exhibition. Yöjuna = Night train : surrealist routes to Kiasma's collections. KIASMA (Museum of Contemporary Art) Helsinki. 2003-03-15. 2004-02-29
boek